Germany divided : from the wall to reunification - McAdams, Arthur James, 1954- 1954- (Princeton studies in international history and politics, 1993)
Germany Divided is the first comprehensive scholarly interpretation of the forty-year relationship between East and West Germany and of the problems of contemporary German unity. When the Berlin Wall was opened on November 9, 1989, there was widespread surprise at the rush to unification: Germany was reuniting just when almost everyone, political participant and observer alike, had become accustomed to it being divided. In this politically controversial and analytically sophisticated account, A. James McAdams dissects the complex process by which East and West German leaders moved over the years from first pursuing the ideal of German unity, to accepting what they believed to be the inescapable reality of division, and then, finally, to meeting the challenges of an unanticipated reunification. In addition to relevant primary and secondary materials, including archival holdings in both German states, McAdams draws on an unprecedented series of interviews conducted throughout the 1980s and early 1990s with officials of the Federal Chancellery, the Foreign Office, and the Ministry of Intra-German Relations of the Federal Republic in Bonn, and the Ministry of Foreign Affairs and the SED Central Committee of the German Democratic Republic in East Berlin. With this unique access to information on high-level decision making, he chronicles an era when the restoration of German unity appeared anything but assured.